Reindeer herding and other traditional means of livelihood in modern context — planning a study in a Sami area in Finland - Heikkilä, Lydia (Rangifer, 2002)
Reindeer herding and other traditional means of livelihoods are challenged in numerous ways by modernization and globalization processes today. In my sociological study, I am aiming at uncovering and analyzing the manifold socio¬economic changes and their contextual social and historical links, that influence the present conditions of practicing reindeer herding as a traditional means of livelihood in Finnish Lapland. In addition to focus on land use, my study will give some new understanding of the local environmental management. This article puts the subject in the current socio-economic developments and social scientific discourses around globalization, environmentalism and traditional knowledge. Moreover I will reflect upon methodology and impact for research results.